THE ROLE OF SODIUM–GLUCOSE COTRANSPORTER-2 (SGLT2) INHIBITORS IN REDUCING THE RISK OF CARDIOVASCULAR EVENTS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS : A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND PRIMARY STUDIES - Diani Nur Pathona (International Medical Journal Corp. Ltd, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) confers a two- to four-fold excess risk of atherosclerotic cardiovascular disease, heart failure, and cardiovascular death. Sodium-glucose cotransporter-2 (SGLT2) inhibitors unexpectedly demonstrated cardiovascular benefit in dedicated cardiovascular outcome trials (CVOTs). This systematic review quantified the effect of SGLT2 inhibition across the full spectrum of cardiovascular events in T2DM patients. Methods: A systematic review was performed per PRISMA 2020 guidelines. Eligible studies were phase III/IV randomized, placebo-controlled trials of SGLT2 inhibitors (empagliflozin, dapagliflozin, canagliflozin, ertugliflozin, sotagliflozin) enrolling adults with T2DM, with adjudicated cardiovascular endpoints and ≥6 months follow-up. Two reviewers independently screened, extracted data, and appraised risk of bias using Cochrane RoB 2. Certainty was rated using GRADE. Pooled estimates used generic inverse-variance random-effects meta-analysis. Results: Twenty-one reports (17 distinct trials; 105,000 participants) met inclusion criteria. Pooled hazard ratios demonstrated: three-point MACE 0.89 (95% CI 0.84–0.94; p<0.0001; I²=0%), cardiovascular death 0.85 (95% CI 0.77–0.93; p<0.001; I²=40.3%), all-cause mortality 0.80 (95% CI 0.70–0.91; p<0.001), hospitalization for heart failure 0.68 (95% CI 0.61–0.76; p<0.0001; I²=0%), composite of cardiovascular death or heart failure hospitalization 0.78 (95% CI 0.75–0.82; p<0.0001; I²=0%), and composite kidney outcome 0.65 (95% CI 0.59–0.71; p<0.0001). Benefit magnitude was greatest for heart failure and kidney endpoints, intermediate for mortality, and modest for atherothrombotic endpoints; stroke was not significantly affected. Safety signals comprised genital mycotic infection and diabetic ketoacidosis; isolated amputation signal from CANVAS was not replicated. Discussion: The findings support a robust, reproducible class-wide cardioprotective effect of SGLT2 inhibition, disproportionately driven by heart failure and cardiorenal protection. Relative benefit is preserved across baseline glycemia, kidney function, albuminuria, ejection fraction, age, sex, and background therapy, while absolute benefit scales with baseline risk. Conclusion: SGLT2 inhibitors significantly and consistently reduce cardiovascular events in T2DM, with strongest effects on heart failure hospitalization, cardiorenal outcomes, and mortality. These agents should be regarded as foundational organ-protective therapy initiated based on cardiorenal risk irrespective of glycated hemoglobin.